What of the Night? Conceptions and Theology of Night in Isaiah and the Book of the Twelve - Funlola Olojede (Old Testament Essays, 2019)
Even though a number of studies have probed the concept of time in the Hebrew Bible, very little has been said about night as a unit of time. This article investigates the conceptions and theology of night in Isaiah and in the Book of the Twelve (Minor Prophets). Whereas strong existential correspondence between day and night is found throughout Isaiah which describes certain negative and positive activities that occur in the night, not all the books in the Book of the Twelve mention the word night. It is argued that the conceptions of night as depicted through the night-time activities and actors (which include God, prophets, watchers, the people of Israel, etc.) have implications for the theology and the worldviews expressed in these prophetic books.